2021
DOI: 10.1038/s41398-021-01255-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin signaling mediates the acute and sustained antidepressant effects of subanesthetic ketamine

Abstract: Subanesthetic ketamine evokes rapid antidepressant effects in human patients that persist long past ketamine’s chemical half-life of ~2 h. Ketamine’s sustained antidepressant action may be due to modulation of cortical plasticity. We find that ketamine ameliorates depression-like behavior in the forced swim test in adult mice, and this depends on parvalbumin-expressing (PV) neuron-directed neuregulin-1 (NRG1)/ErbB4 signaling. Ketamine rapidly downregulates NRG1 expression in PV inhibitory neurons in mouse medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…The epidermal growth factor family member neuregulin-1 (NRG1) and its receptor ErbB4 play a role in the regulation of inhibitory neural circuits in the PFC [ 138 ]. A recent study showed that the rapid and sustained antidepressant-like effects of ( R,S )-ketamine may be mediated through cortical disinhibition via PV-specific NRG1 signaling in the medial PFC [ 139 ]. Future studies using rodents with depression-like phenotypes are also required to confirm the role of NRG1 in the antidepressant-like effects of ( R,S )-ketamine and its enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…The epidermal growth factor family member neuregulin-1 (NRG1) and its receptor ErbB4 play a role in the regulation of inhibitory neural circuits in the PFC [ 138 ]. A recent study showed that the rapid and sustained antidepressant-like effects of ( R,S )-ketamine may be mediated through cortical disinhibition via PV-specific NRG1 signaling in the medial PFC [ 139 ]. Future studies using rodents with depression-like phenotypes are also required to confirm the role of NRG1 in the antidepressant-like effects of ( R,S )-ketamine and its enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…After exposure to ketamine, a glutamate burst in the synapse is observed, and this is thought to be caused by the binding of ketamine to inhibitory interneurons and thereby enhancing the actions of pyramidal excitatory neurons ( 24 28 ). Downstream signaling molecules of this process, such as neuregulin-1, has shown to be downregulated post ketamine administration in parvalbumin-expressing (PV) interneurons, resulting in cortical disinhibition ( 29 ). In addition, this glutamate burst is not observed with traditional antidepressants ( 24 28 , 30 ), though it seems to be dependent on specific synapses and is not globally observed ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…We then demonstrate the effectiveness of SCOUT on a set of simulated datasets, consisting of the Gaussian dataset (control dataset, low background noise levels; Figure S1 A and STAR Methods ), the Non-Rigid 1-photon (1p) dataset (variable sized spatial footprints warped in place by generated non-rigid transformation, high background noise levels; Figure S1 B), the Non-Rigid 2-photon (2p) dataset (modified version of the Non-Rigid 1p dataset in which footprint centers are removed to simulate characteristic ring shapes, salt and pepper noise; Figure S1 C), and the Individual Shift dataset (spatial footprints individually translated a random distance, no background noise; Figure S1 D). We also test SCOUT on 1-photon experimental data from the visual cortex (VC) ( Grieco et al., 2020 ), the prefrontal cortex (PFC) ( Grieco et al., 2021 ), and the hippocampus (Hipp) ( Sun et al., 2019 ) ( Figure S1 E), which exhibit strong variation in neural signals due to experimental conditions ( STAR Methods ), as well as three 2-photon recordings taken from the visual cortex ( Allen, 2016 ) labeled VISl, VISrl, and VISp ( Figure S1 F), taken as head-fixed mice were shown various stimuli ( STAR Methods ) causing neural signal variability. Finally we test place-field stability of neurons identified by SCOUT on three 1-photon recordings taken from the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…The prefrontal cortex recording was subject to the following protocol ( Grieco et al., 2021 ). An initial pair of baseline recordings were taken on consecutive days.…”
Section: Methodsmentioning
confidence: 99%